Teachers' Experiences in Using Digital Media to Enhance Elementary Students' Learning Enthusiasm - Nufus, Ayatun; Haifaturrahmah; Muhammad Nizaar (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe teachers’ experiences in using digital media to enhance elementary students’ learning enthusiasm. A descriptive qualitative approach was applied with data collected through in-depth interviews, direct observations, and documentation. Informants were selected purposively, focusing on teachers who have direct experience in integrating digital media in the classroom. Data were analyzed using Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The findings reveal that digital media such as videos, interactive animations, and educational applications effectively attract students’ attention, increase active participation, and strengthen conceptual understanding. However, challenges such as limited facilities, unstable internet access, and varying levels of teachers’ technological competence remain obstacles. Teachers’ creativity and pedagogical reflection are key factors in the successful integration of technology. This research emphasizes the importance of enhancing teachers’ digital competence to create innovative, engaging, and adaptive learning in the digital era.